314 trainees from 5 public universities commissioned as Inspector of Police Undergraduate Voluntary Corps - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 24 September 2022 - A total of 314 Inspectors of the Police Undergraduate Voluntary Corps (SUKSIS) were commissioned after completing training conducted for three years or six semesters involving 672 hours following the training syllabus that has been coordinated and established at public universities (UA).